2007
DOI: 10.1021/es071281e
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Halogen Additions on Mercury Oxidation, in A Slipstream Selective Catalyst Reduction (SCR), Reactor When Burning Sub-Bituminous Coal

Abstract: This paper presents a comparison of impacts of halogen species on the elemental mercury (Hg(0)) oxidation in a real coal-derived flue gas atmosphere. It is reported there is a higher percentage of Hg(0) in the flue gas when burning sub-bituminous coal (herein Powder River Basin (PRB) coal) and lignite, even with the use of selective catalytic reduction (SCR). The higher Hg(0)concentration in the flue gas makes it difficult to use the wet-FGD process for the mercury emission control in coal-fired utility boiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(82 citation statements)
references
References 14 publications
1
81
0
Order By: Relevance
“…4a are probably because of the bromine content of coal. There is evidence that bromine species are capable of enhancing the conversion of Hg 0 to Hg 2+ (Liu et al, 2007;Cao et al, 2008b;Niksa et al, 2009). We found there was significant correlation between the Hg 2+ percentage in flue gas released from the tested boilers and the bromine content of coal (see Fig.…”
Section: Mercury Release From Coal Combustionmentioning
confidence: 99%
“…4a are probably because of the bromine content of coal. There is evidence that bromine species are capable of enhancing the conversion of Hg 0 to Hg 2+ (Liu et al, 2007;Cao et al, 2008b;Niksa et al, 2009). We found there was significant correlation between the Hg 2+ percentage in flue gas released from the tested boilers and the bromine content of coal (see Fig.…”
Section: Mercury Release From Coal Combustionmentioning
confidence: 99%
“…Increasing the concentration of chlorine in the combustion process facilitates the creation of Hg +2 [4,42]. The amounts of chlorine in Polish hard coals and lignites are derived from studies: [1] and [9].…”
Section: Chlorine Content In Fuelmentioning
confidence: 99%
“…The technological structure of APC devices applied before 2010 [47] based on data derived from the ENVIRO database is comparable with data included in this paper. Basing on uncertainty range: A, average estimation; B, low estimation; C high estimation; , no estimation made for 1990 Based on available elaborations [4,17,32,37], also papers and guidelines on uncertainty assessment [10, 13,40,46], the mercury removal efficiencies are assigned with a 30% uncertainty range. Results are presented in Table 13.…”
Section: Assumed Apcs' Efficienciesmentioning
confidence: 99%
“…Pilot-scale results obtained by Cao et al [82] revealed that, in the presence of different commercial SCR catalysts and under PRB (power river basin coal with low sulfur and chlorine contents) coal-derived flue gases, Hg el oxidation was enhanced by the addition of hydrogen halides in the following order: HBr, HI, and HCl or HF. However, it must be considered that the measurement of Hg [21,25,78,83].…”
Section: Influence Of Flue Gas Constituentsmentioning
confidence: 99%